Rola króla w Izraelu w stosunku do ojcostwa Boga i do społeczeństwa w kontekście starożytnego Bliskiego Wschodu - Waszak, Piotr (Verbum Vitae, 2011)
The understanding of the origins, functions and duties of a monarchy in the ancient world was influenced by religious beliefs current at that time. This „theology” fundamentally impinged on the establishment of the concept and the character of „royal paternity” having previously determined the relations between the king himself and the supernatural world. According to biblical sources, at the time when Israel was a monarchy, it is possible to state that there was a specific awareness of the role of the king that consisted in stipulating the covenant between the nation and God. This demanding and charismatic model has been embodied and realised not until the moment when Messiah – the King who perfectly revealed God’s fatherhood